2020
DOI: 10.1371/journal.pone.0233783
|View full text |Cite
|
Sign up to set email alerts
|

Crop management system and carrot genotype affect endophyte composition and Alternaria dauci suppression

Abstract: Managing pests in carrot production is challenging. Endophytic microbes have been demonstrated to improve the health and productivity of many crops, but factors affecting endophyte dynamics in carrot is still not well understood. The goal of this study was to determine how crop management system and carrot genotype interact to affect the composition and potential of endophytes to mitigate disease caused by Alternaria dauci, an important carrot pathogen. Twenty-eight unique isolates were collected from the tapr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 117 publications
1
9
0
Order By: Relevance
“…The results of this study suggest that plant-soil microbe interactions are influenced by trait breeding in organic carrot. This aligns with previous findings that carrot genotypes host distinct root-associated microbiomes that potentially differ in their functionality (Triviño et al 2023, Abdelrazek et al 2020. Moreover, we show that root exudation patterns were distinct across genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study suggest that plant-soil microbe interactions are influenced by trait breeding in organic carrot. This aligns with previous findings that carrot genotypes host distinct root-associated microbiomes that potentially differ in their functionality (Triviño et al 2023, Abdelrazek et al 2020. Moreover, we show that root exudation patterns were distinct across genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…40°17′21″ N. long. 86°53′02″), located approximately 10 miles south of Lafayette, IN during summer 2015 48 . Soil at this site is classified in the Drummer soil series, which typically contain approximately 3.2% organic matter and a neutral pH.…”
Section: Methodsmentioning
confidence: 99%
“…Another factor that could enhance the survival and efficacy of beneficial microbial inoculants is varietal or genotype selection. For example, we have previously demonstrated that both tomato (Jaiswal et al., 2020) and carrot (Abdelrazek et al., 2020) genotypes vary in their capacity to benefit from beneficial microbial inoculants. In this trial, we also observed a genotypic response, with fewer deaths in the tomato cultivar W55, but not Corbarino, because of inoculation with T‐22 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%